Peningkatan Skill Komunikasi Interpersonal Mahasiswa dalam Upgrade Kualitas Profil Lulusan - Ayu Rahma Nengsi; Didi Sartika (FONDATIA, 2022)
This research is motivated by the needs of users for the profile of college graduates, one of the soft skills that is considered important in today's labor market is communication skills. This research is intended to facilitate students' communication skills as a provision for future careers. The participants who fulfilled the invitation were 28 3rd and 4th year students. The training focused on 3 main aspects of communication skills such as listening, speaking and writing. Evaluation is carried out in three stages, namely: pre-test, during the process and post-test. Research shows that training can improve participants' communication skills, especially listening and speaking skills. Capturing information that is heard correctly is very important in effective communication activities, where almost 50% of activities that occur in communication are listening. The ability to speak improved better when the participants had sufficient understanding of the material and the topic, and the main problem in this speaking ability lies in the participants' low self-confidence and courage, but this can be improved with continuous practice. Meanwhile, writing communication skills need more intense training and must become a habit in lecture activities, so that the tips learned in the training can be applied on an ongoing basis.